Taxonomic considerations about the paleo-ichthyofauna of the locality of Alto Guayacán, Uscari Formation, late Miocene-early Pliocene [N17 a N19]: record of the genus Parascyllium - Calvo, Cristian (2023)
The genus Parascyllium is recorded for the first time for the Cenozoic of the Caribbean and Neotropical America Region. Currently the 5 extant species of the genus are restricted to southern Australian waters, and the worldwide fossil records of Parascyllium are extremely scarce, which is why the Costa Rican fossil record is such a significant finding.